Efficient in vivo labeling of endogenous proteins with SMART delineates retina cellular and synaptic organization - Chuanping Zhao; Yan Cao; Noor Ibrahim; Yuchen Wang; Kirill A. Martemyanov (Nature Communications)
Abstract A key application of CRISPR/Cas9-based genomic editing is modification of genes to introduce engineered sequences. However, the editing flexibility is severely constrained by the requirement for targeting sites in proximity to the desired modification site, which makes many modifications intractable. Here, we develop a strategy that overcomes this key limitation to allow CRISPR-based editing at any position with high efficiency. It relies on reconstructing the targeted gene using Silently Mutate And Repair Template (SMART) where we mutate the gap sequence in the repair template to prevent its base pairing with the target DNA while maintaining the same amino acid coding. Using vertebrate retina as a neuronal model system we document the application of SMART editing for labeling endogenous proteins in vivo with high efficiency. We show that SMART editing allows us to access numerous cell types in the retina and address fundamental cell biological questions pertaining to its organization. We propose that this approach will facilitate functional genomic studies in a wide range of systems and increase the precision of corrective gene therapies.